(untitled) (Communication & Society, 2019)
Drawing from 93 semi-structured, in-person interviews with journalists from 23 states, this article analyzes the relation between trust and risk perception in Mexican journalism. It focuses on how Mexican journalists perceive and experience public trust placed in them as social actors, and how it influences their willingness or reluctance to assume the risks associated with reporting on corruption and drug-trafficking in a country marked by anti-press violence. The findings challenge previous studies as they show that journalists from all regions of the country –even in the so-called safe states– are fearful, even when they have not been victims of threats, beatings or kidnappings. Also, it explains that the connection between institutions and journalism makes news workers feel unprotected and unaccompanied. As a result, they accept self-censorship and even express a willingness to resign. Thus, this article surpasses the social, spatial and temporal delimitations of risk, by arguing that distrust in journalists increases the dangers they face.